PARP2 downregulation in T cells ameliorates lipopolysaccharide-induced inflammation of the large intestine - Bencsics, Máté; Bányai, Bálint; Ke, Haoran; Csépányi-Kömi, Roland; Sasvári, Péter; Dantzer, Françoise; Hanini, Najat; Benkő, Rita; Horváth, Eszter M. (Frontiers in Immunology, 2023)
T cell-dependent inflammatory response with the upregulation of helper 17 T cells (Th17) and the downregulation of regulatory T cells (Treg) accompanied by the increased production of tumor necrosis alpha (TNFα) is characteristic to inflammatory bowel diseases (IBD). Modulation of T cell response may alleviate the inflammation thus reduce intestinal damage. Poly(ADP-ribose) polymerase-2 (PARP2) plays role in the development, differentiation and reactivity of T cell subpopulations. Our aim was to investigate the potential beneficial effect of T cell-specific PARP2 downregulation in the lipopolysaccharide (LPS) induced inflammatory response of the cecum and the colon. Low-dose LPS was injected intraperitoneally to induce local inflammatory response, characterized by increased TNFα production, in control (CD4Cre; PARP2+/+) and T cell-specific conditional PARP2 knockout (CD4Cre; PARP2f/f) mice. TNFα, IL-1β, IL-17 levels were measured by ELISA, oxidative–nitrative stress was estimated by immunohistochemisty, while PARP1 activity, p38 MAPK and ERK phyosphorylation, and NF-κB expression in large intestine tissue samples were examined by Western-blot. Systemic & local T cell subpopulation; Th17 and Treg alterations were also investigated using flow-cytometry and immunohistochemistry. In control animals, LPS induced intestinal inflammation with increased TNFα production, while no significant elevation of TNFα production was observed in T cell-specific PARP2 knockout animals. The absence of LPS-induced elevation in TNFα levels was accompanied by the absence of IL-1β elevation and the suppression of IL-17 production, showing markedly reduced inflammatory response. The increase in oxidative-nitrative stress and PARP1-activation was also absent in these tissues together with altered ERK and NF-κB activation. An increase in the number of the anti-inflammatory Treg cells in the intestinal mucosa was observed in these animals, together with the reduction of Treg count in the peripheral circulation. Our results confirmed that T cell-specific PARP2 downregulation ameliorated LPS-induced colitis. The dampened TNFα production, decreased IL-17 production and the increased intestinal regulatory T cell number after LPS treatment may be also beneficial during inflammatory processes seen in IBD. By reducing oxidative-nitrative stress and PARP1 activation, T cell-specific PARP2 downregulation may also alleviate intestinal tissue damage.